Correction: A natural history study to track brain and spinal cord changes in individuals with Friedreich's ataxia: TRACK-FA study protocol. - Nellie Georgiou-Karistianis; Louise A Corben; Kathrin Reetz; Isaac M Adanyeguh; Manuela Corti; Dinesh K Deelchand; Martin B Delatycki; Imis Dogan; Rebecca Evans; Jennifer Farmer; Marcondes C França; William Gaetz; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0269649.].